Involvement of the E2-like enzyme Atg3 in fungal development and virulence of Botryosphaeria dothidea - Han, Wenjiao; Han, Yang; Ma, Yanru; Yu, Guolei; Jiang, Xushi; Yang, Qian; Liu, Na; Wang, Caixia; Li, Baohua; Lian, Sen; Ren, Weichao (Frontiers in Plant Science, 2025)
Autophagy is a fundamental cellular degradation and recycling system that is crucial for maintaining cellular homeostasis, responding to stress, and ensuring the proper functioning of cells. To date, the biological functions of autophagy in the plant-pathogenic fungus Botryosphaeria dothidea remains largely unknown. In this study, we identified and characterized the E2-like enzyme Atg3 in B. dothidea. The autophagic process was blocked in the BdATG3 deletion mutant ΔBdAtg3, and the ΔBdAtg3 mutant showed serious defects in mycelial growth, conidiation, perithecium formation and virulence. In addition, the ΔBdAtg3 mutant exhibited an increased number of nuclei in mycelial compartment. All of the phenotypic changes of the ΔBdAtg3 mutant were restored by gene complementation. These results indicate that the E2-like enzyme Atg3 plays an important role in various developmental processes and pathogenesis of B. dothidea, which provides a potential target for developing novel fungicides.